Phytochemical characterization, anticancer potential, and nanoemulsion-based delivery of Chiliadenus montanus - Nour Aboalhaija; Hala Abulawi; Rania Hamed; Mohammad Alwahsh; Fatma Afifi; Heba Syaj; Elham Abusharieh; Ismail Abaza (PLoS ONE, 2025)
Chiliadenus montanus (Vahl) Boiss. (Asteraceae) is a pharmacologically significant plant with different potent pharmacological properties. This study aimed to evaluate the phytochemical and anticancer activity of C. montanus, and to develop nanoemulsions (NEs) to enhance pulmonary delivery for lung carcinoma treatment. For that ethanol and water extracts, along with petroleum ether, chloroform, ethyl acetate, and methanol fractions, were assessed for total phenol and flavonoid contents, antioxidant activity, and cytotoxicity against H1299 and A549 lung cancer cell lines. The results showed that ethyl acetate fraction exhibited the highest phenol (47.94 ± 0.32 mg GAE/g of DW) and flavonoid (20.34 ± 1.48 mg rutin/g of DW) contents, while the ethanol extract showed the most potent antioxidant activity (IC₅₀ = 322.1 µg/mL) and selective cytotoxicity (IC₅₀ = 641.2 µg/mL) against H1299 cells. Nevadensin, chlorogenic acid, and sorbifolin were identified as the major constituents of the ethanol extract using liquid chromatography-mass spectrometry (LC-MS) analysis. Gas chromatography-mass spectrometry (GC-MS) analysis revealed α-phellandrene, 1,8-cineole, and α-cadinol as the lead volatile constituents. The major volatile compound of the aroma profile of the aerial parts, determined by solid phase micro extraction (SPME) was 1,8-cineole. Spontaneous emulsification was used to formulate ethanolic NE (S1-S4 NEs) with varying concentrations of ethanol extract, surfactant, cosurfactant, and oil phase. The optimal S4 NE demonstrated thermodynamic stability, appropriate pulmonary pH, and droplet sizes below 100 nm. These findings highlight the promising potential of C. montanus NE as a stable pulmonary drug delivery system for lung carcinoma therapy.